Pengaruh Market Share Investasi Mura>bah}ah pada Usaha Mikro dan Kecil Terhadap Profitabilitas Bank Syariah Mandiri Cabang Bone - Alfian Alfian (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2019)
The purpose of this study is to determine the effect of market share mura bah} ah investment in micro and small businesses on the profitability of the Bank Syariah Mandiri Branch Bone. This research is a quantitative study using the census method. Data obtained through observation, questionnaires and documentation were then processed using the chi-square formula in SPSS 21 for Windows. The results showed that the market share of mura bah} ah investment in micro and small businesses had a significant effect on the profitability of the Bone Branch of Bank Syariah Mandiri.